2015
DOI: 10.1002/celc.201500133
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Vertical Displacement of Lithiated Silicon Particles in High Volumetric Capacity Battery Electrodes

Abstract: Silicon is ap otential high-capacity anode material for lithiumion batteries. However,l arge volume changesi nt he material remains ab ottleneck to its commercialization. Many works have been devoted to nanostructured composites with voids to accommodate the volumee xpansion. Yet, the full capability of silicon cannot be utilized, because these nanostructured electrodes have low volumetric capacities. Herein, we redesign dense silicon electrodes with three times the volumetric capacity of graphite. In situ ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 43 publications
4
52
0
Order By: Relevance
“…This is a strong indication that the pH of the slurry has a major impact on the efficiency of the CMC binder to limit the cohesion loss of the electrode architecture with cycling. This is also supported by comparing the present work with the recent electrochemical dilatometry study of Yu et al 32 showing, under nearly similar experimental conditions, a total thickness expansion after full lithiation as high as 450% for a Si/C/CMC (60/20/20) composite electrode prepared at natural pH. By comparing Si-based electrodes prepared with different binders (PVdF, CMC and polyimide), they have shown that these have a major impact on the dilatometric behavior of the electrode.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This is a strong indication that the pH of the slurry has a major impact on the efficiency of the CMC binder to limit the cohesion loss of the electrode architecture with cycling. This is also supported by comparing the present work with the recent electrochemical dilatometry study of Yu et al 32 showing, under nearly similar experimental conditions, a total thickness expansion after full lithiation as high as 450% for a Si/C/CMC (60/20/20) composite electrode prepared at natural pH. By comparing Si-based electrodes prepared with different binders (PVdF, CMC and polyimide), they have shown that these have a major impact on the dilatometric behavior of the electrode.…”
supporting
confidence: 91%
“…[20][21][22] In recent years, several studies of Si-based anodes have integrated some electrochemical dilatometry results. 16,[23][24][25][26][27][28][29][30][31][32] However, the dilatometric responses are rarely analyzed in detail.The role of the binder is very critical for Si electrodes to maintain the electrode architecture despite the large Si volume change and thereby to achieve long cycle life.8 Although carboxymethyl cellulose * Electrochemical Society Member. z E-mail: roue@emt.inrs.ca (CMC) is not an elastomeric binder, it has been shown to significantly improve the cycling performance of Si electrodes.…”
mentioning
confidence: 99%
“…13 This further verifies that the amount of binder is a critical variable affecting electrode performance. These results suggest that to improve mechanical and electrochemical stability of a Si electrode, one should increase the amount of binder, choose a stronger binder and limit the discharge capacity.…”
Section: Methodsmentioning
confidence: 65%
“…Since the Si material used in both electrodes are the same, the difference in coulombic efficiency is not due to the material (surface or bulk), but to the strength of the binder, as PI is known to be stronger than CMC. 13,[27][28][29] Our results suggest that about 2-3% of the irreversibility of the Si-CMC electrodes comes from mechanical problems in the electrode. Figures 9c and 9d show the cycle performance of Si-CMC and Si-PI electrodes with 1000 mAh g −1 capacity limitation.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation